Experiments in Artificial Sociality : Curious robots, relational configurations, and dances of agency - Vejlin, Frederik (STS Encounters, 2021)
In this article, I explore how experiments with social robots enact and reconfigure more-than-human forms of sociality. I combine recent anthropological discussions of nonhuman sociality with Andy Pickering’s work on dances of agency (1993, 1995) and John Law’s method assemblages (2004) to show how human-robot interaction experiments enact open-ended and decentred configurations of entangling relations between humans and robots. I propose the concept of artificial sociality to capture both the ongoing enactments and multiple results of such experimental reconfigurations. Using these conceptual tools, I unpack the “curious robot experiment” from my ethnographic fieldwork in a Japanese robotics laboratory and compare the kinds of sociality produced in the two experimental conditions. I argue that the curious robot exemplifies what Pickering calls technologies of engagement (2018) by manifesting a form of artificial sociality that augments the unpredictability of dances of agency enacted in (re)configurations of entangling relations.